Analysis of risk factors for sternal surgical site infection: Emphasizing the appropriate ventilation of the operating theaters - AYKAÇ, ZEYNEP ZUHAL (CAMBRIDGE UNIV PRESS, 2006)
objective. To determine the incidence of and identify risk factors for sternal surgical site infection ( SSI). design. Prospective cohort study. Data on potential risk factors, including the type of operating theater and infection data, were collected prospectively and analyzed by multivariate analysis. setting. Siyami Ersek Thoracic and Cardiovascular Surgery Hospital, a 700- bed teaching hospital and the largest center for cardiac surgery in Turkey. The cardiothoracic unit performs approximately 3,000 cardiac operations per year. patients. All adult patients who underwent cardiac surgery with sternotomy between January 14, 2002, and July 1, 2002, and who survived at least 4 days after surgery were included in the study. results. Potential risk factor data were complete for 991 patients. There was sternal SSI in 41 patients ( 4.1%). Female sex, diabetes mellitus, operation performed in the older operating theaters, and duration of procedure exceeding 5 hours were identified as independent risk factors for sternal SSI. conclusions. Female and diabetic patients are at higher risk for sternal SSI and should be followed up carefully after cardiac surgery to prevent the development of sternal SSI. Reducing the duration of surgery could reduce the rate of postoperative sternal SSI. The operating theater environment may have an important role in the pathogenesis of sternal SSI, and appropriate ventilation of the operating theaters would be critical in the prevention of sternal SSI.
Keywords: WOUND-INFECTION; DEEP; COMPLICATIONS; SURGERY; INDEX